The Effectiveness of Group Work in Enhancing Students' Writing Skill: The Case of Second Year Students at Souk- Ahras University - Hakima Meras (My University, 2022)
Abstract The main concern of the current study is that writing in a foreign language has always been a challenging skill for EFL learners to master, for those reasons teachers always look for what might help students increase their proficiency in writing. Accordingly, the present study aims to scrutinize the effectiveness of using group work in enhancing students' writing skill. In other words, the work checks the correlation between the implementation of group work in EFL classrooms and the development of students' writing production. The descriptive method has been adopted using questionnaire for second year EFL students and a structured interview for their teachers at the department of English in Soukahras University. The analysis of the gathered data have illustrated that group work have an effective impact on improving the writing abilities of students, enhance their writing production, and solve many faced problems. Based on the obtained results, the hypothesis is confirmed.